Epic honour and shame in the Mahabharata and the Iliad: Cultural reflections of warrior ethics (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Both the Mahabharata and the Iliad examine the notions of honour and shame as major themes that drive the actions and motives of its characters, so influencing their destiny and the course of events. However, the Mahabharata emphasizes the concept of honour, while the Iliad emphasizes the concept of shame. The main aim of this paper is to discuss the Honour and Shame in the Mahabharata and the Iliad: Cultural Reflections of Warrior Ethics in which we mainly discuss about the importance or role of honour and shame and cultural values through customs in both the epics. It is stated that the Mahabharata and the Iliad explore the significance of honour and shame in shaping character motivations and societal values. While the Mahabharata ties honour to dharma and duty, the Iliad emphasizes personal glory and reputation. Despite cultural differences, both epics highlight how the pursuit of honour often leads to conflict and loss, offering timeless lessons on ethics, duty, and the consequences of human choices.